Immune activation of characteristic gut mycobiota Kazachstania pintolopesii on IL-23/IL-17R signaling in ankylosing spondylitis - Zhang, Haiting; Wei, Yu; Jia, Huanhuan; Chen, Diling; Tang, Xiaocui; Wang, Jian; Chen, Meili; Guo, Yinrui (Frontiers in Cellular and Infection Microbiology, 2022)
It is very important to understand the communication and interaction mechanisms between the host and its resident microorganisms on host physiology and for precise diagnosis and treatment. Although intestinal fungi and bacteria dysbiosis is increasingly linked to ankylosing spondylitis (AS), their mechanisms of action have been rarely illustrated. In this paper, fecal samples from 10 AS monkeys and 10 healthy controls were collected to systematically characterize the gut mycobiota and microbiota in AS monkeys by 16S rRNA and ITS2 DNA sequencing. Our results showed the gut fungi of Kazachstania pintolopesii, Saccharomycetaceae, Kazachstania, and Saccharomyceteles. Saccharomycetes were specially enriched in AS, and the microbiota of AS monkeys was characterized by an increased abundance of Clostridia, Clostridiales, Ruminococcaceae, and Prevotella 2, using Line Discriminant Analysis Effect Size. Compared to healthy controls, decreased ITS2/16S biodiversity ratios and altered bacterial–fungal interkingdom networks were observed in AS monkeys. Oral administration of K. pintolopesii activates IL-17RA pathway and induce inflammatory reaction in the colonic tissue of C57BL/6 mice, as well as multiple AS phenotypes, including fungal and bacterial dysbiosis, immune responses of NK cells, platelets, T cells, leukocytes, B-cell activation, rheumatoid arthritis, and inflammatory bowel disease. We also found the secreted products of K. pintolopesii could activate the IL-17RA pathway, which induces PANoptosis in macrophage RAW264.7 cells. Much worse, the PANoptosis products could promote the proliferation and morphological changes of K. pintolopesii, which resulted in much more K. pintolopesii and a severe inflammatory reaction. Interestingly, the inflammatory factor TNF-α can promote the morphological transformation of Candida albicans and K. pintolopesii, which is worthy of further study. The characteristic fungi in all these findings implied that fungal and bacterial dysbiosis have a close link to AS and that their communication and interaction indeed play an important role in autoimmune responses, and K. pintolopesii could be a potential marker microorganism in AS, although its specific mechanism is not fully elucidated.